Questioning styles in the Qur’ān and their impact on human thinking a conceptual analysis - Badi, Jamal Ahmed Bashier; Machouche, Salah; Bensaid, Benaouda (IIUM Press, International Islamic University Malaysia, 2017)
Questions and questioning represent one of the most important communicative and illustrative mediums of the Qur’an. Qur’ān exegetes devoted significant effort to the study of styles of questioning across various disciplines of the Qur’ān sciences, and as such, have addressed the topic of questions from the perspectives of language, theology, jurisprudence, dialectics, philosophy and ethics. Little interest, however, is shown to the relationship between questions and thinking. This textual analysis of selected Qur’ānic questions examine Qur’anic questions, their forms, scope, functions and effects with respect to development of human thought. This study shows that questions in the Qur’ān serve a broad range of objectives. The style of questioning inherent the Qur’ān presents an intuitive and familiar method that may be further invested in current Muslim education and learning to revive critical thinking and creativity know to early Generation.